El proceso formativo y transformador de la práctica pediátrica de docentes del Área de Niñez: Facultad de Medicina de la Universidad de Antioquia. - Salazar-Blanco, Olga Francisca; Gómez-Gómez, Margarita María; Zuliani-Arango, Liliana Adela (Revista Facultad de Medicina de la Universidad Nacional de Colombia, 2016)
Background. Pediatric practice has certain particularities that should be taken into account in the training of undergraduate Medicine students under the biopsychosocial approach. This promotes the understanding of the communicative universe that takes place in the child-caregiver-professional triad. Previous studies indicate certain influence of teachers in the students' process of learning of this interaction. Objective. To recognize both the formative and transformative processes of the pediatric practice of teachers of the Childhood Department at the Facultad de Medicina, Universidad de Antioquia. Materials and Methods. A qualitative study with symbolic interactionism approach was performed. 19 teachers participated in this study. A semistructured interview was applied. Data analysis was done under the guidelines of the grounded theory. Results. Three categories were revealed: 1) how teachers became doctors and pediatricians: emphasizing their teachers as models; 2) what transforms their practice: time, expertise, institutions and working groups; 3) the resources used by teachers regarding interactions with the child and the family in different health attention scenarios: the question, observation, explanation, games and health education. Conclusion. Interviewed teachers took as a learning model their teachers practices on the child-caregiver-professional communication triad. However, their practice reflection has changed their communication process. University health education should promote self-reflection on the interaction models that teachers offer to their students.